A simple pendulum studied with a low-cost wireless acquisition board - Alho, J. (2019)
In the field of physics teaching, the simple pendulum provides a very simple way to study the harmonic oscillator, the source of some fundamental concepts such as periodicity, relaxation time and anharmonicity. As such, its experimental study is frequently integrated into high school or first year university programs. With this in mind, in this article, we propose a simple setup allowing the study of some of its properties. By coupling a small wireless acquisition board to an oscillating mass, the centripetal acceleration is recorded and analyzed. We show using basic calculations how this acceleration allows us to extract the variation with time of its period and of the amplitude. The experimental results show that the damping of the amplitude is very well described by an exponential law. The accuracy we obtain on the period allows us to show that, not only does it decrease with amplitude, but that this decrease is relatively well described by standard calculation. Using wireless multipurpose acquisition board and usual spreadsheet for experimental modelling, the completion of this work, about 4 h, offers to the student an original way to go a little beyond the classical study of the spectacular object that is the pendulum.